Association between endothelin type A receptor haplotypes and mortality in coronary heart disease. (May 2012) - Ellis, Katrina L; Pilbrow, Anna P; Potter, Howard C; Frampton, Chris M; Doughty, Rob N; Whalley, Gillian A; Ellis, Chris J; Palmer, Barry R; Skelton, Lorraine; Yandle, Tim G; Troughton, Richard W; Richards, A Mark; et al.
Aims: The endothelin type A receptor, encoded by EDNRA, mediates the effects of endothelin-1 to promote vasoconstriction, vascular cell growth, adhesion, fibrosis and thrombosis. We investigated the association between EDNRA haplotype and cardiovascular outcomes in patients with coronary artery disease.Methods: Coronary disease patients (n = 1007) were genotyped for the His323His (rs5333) variant and one tag SNP from each of the major EDNRA haplotype blocks (rs6537484, rs1568136, rs5335 and rs10003447). EDNRA haplotype associations with clinical history, natriuretic peptides cardiac function and cardiovascular outcomes were tested over a median 3.8 years.Results: Univariate analysis identified a 'low-risk' EDNRA haplotype associated with later age of Type 2 diabetes onset (p = 0.004) smaller BMI (p = 0.021), and reduced mortality (log rank p = 0.001). Cox proportional hazards analysis including established cardiovascular risk factors revealed an independent association between haplotype and mortality (p < 0.0001).Conclusion: These data highlight the potential importance of the endothelin system, and in particular EDNRA in coronary disease.